PENGEMBANGAN PANDUAN APLIKATIF PENILAIAN AUTENTIK DALAM PEMBELAJARAN TEMATIK INTEGRATIF DI SEKOLAH DASAR NEGERI KABUPATEN NGANJUK - Rahmania, Nurani (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2021)
This research and development aims to produce a product with the formulation of the problem: (1) Describing the product specifications of the authentic assessment applicative guidebook in class IV integrative thematic learning with the theme Kayanya Negeri ku, (2) Knowing the level of validity of the applicative guidebook for authentic assessment in class IV integrative thematic learning. the theme of Kayanya Negeri ku, and (3) Knowing the teacher's assessment of the applicative guidebook for authentic assessment in integrative thematic learning for class IV with the theme of Kayanya Negeri ku. The method used in this research is the research and development (RnD) method used to produce certain products. The design development of this assessment guide uses the Borg and Gall design model. The research subjects included 5 fourth grade teachers in 4 government target primary schools in implementing the 2013 Curriculum in Nganjuk Regency, namely SDN Banaran 1 Kertosono, SDN Baron 1, SDN Kemaduh 2, and SDN Mabung 2. equipped with an assessment instrument. The development of this assessment guide has obtained a valid qualification level. In the material aspect, the valid percentage is 96.7% and the design aspect is 98%. The teacher's assessment of the product after the trial was very good with the percentage score in the initial trial of 87.6% and in the field trial of 92.8%.